(1)H, (13)C, and (15)N resonance assignments for the tandem PHD finger motifs of human CHD4. - Walport, L; Morra, R; Mancini, E; Redfield, C (Springer Netherlands, 2015)
The plant homeodomain (PHD) zinc finger is a structural motif of about 40-60 amino acid residues found in many eukaryotic proteins that are involved in chromatin-mediated gene regulation. The human chromodomain helicase DNA binding protein 4 (CHD4) is a multi-domain protein that harbours, at its N-terminal end, a pair of PHD finger motifs (dPHD) connected by a ~30 amino acid linker. This tandem PHD motif is thought to be involved in targeting CHD4 to chromatin via its interaction with histone tails. Here we report the (1)H, (13)C and (15)N backbone and side-chain resonance assignment of the entire dPHD by heteronuclear multidimensional NMR spectroscopy. These assignments provide the starting point for the determination of the structure, dynamics and histone-binding properties of this tandem domain pair.